Design of Filterization Monitoring System in Household Wastewater Treatment using IoT Based PID Method - Ahing, Yayan Mutu; Sumarahinsih, Andrijani; Gumilang, Yandhika Surya Akbar (Ilmu Bersama Center, 2024)
This research aims to design and optimize the PID control system for FPV drones using Betaflight software. The main focus of this study is on tuning and adjusting PID parameters to achieve stability, responsiveness and optimal performance of the drone during extreme flight maneuvers. By utilizing Betaflight as the PID tuning platform, this research attempts to fine-tune the optimal values of proportional (P), integral (I), and derivative (D) to obtain precise and agile control responses. Through the optimization of the PID control system, it is expected that FPV drones can achieve high reliability and performance in tackling various flight challenges. The results of this research are expected to contribute to the development of advanced and effective FPV drones in executing complex flight maneuvers.